Earnings, Capital Structure And Market Value - Kain, Wong Chee (2003)
Capital structure and earnings are considered variables that will impact the company's market value. This paper will briefly describe the Modigliani and Miller theory of capital structure introduced by them in 1958 and olso their subsequent correction.